Computational methods in systems biology : International Conference CMSB 2007, Edinburgh, Scotland, September 20-21, 2007 : proceedings - International Conference CMSB 2007 (2007 : Edinburgh, Scotland); Calder, Muffy; Gilmore, Stephen, 1962- (Berlin : Springer-Verlag, 2007)
42